2007
DOI: 10.1103/physrevb.76.241302
|View full text |Cite
|
Sign up to set email alerts
|

Strongly enhanced effective mass in dilute two-dimensional electron systems: System-independent origin

Abstract: We measure the effective mass in a dilute two-dimensional electron system in (111)-silicon by analyzing temperature dependence of the Shubnikov-de Haas oscillations in the low-temperature limit. A strong enhancement of the effective mass with decreasing electron density is observed. The mass renormalization as a function of the interaction parameter rs is in good agreement with that reported for (100)-silicon, which shows that the relative mass enhancement is system-and disorder-independent being determined by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 31 publications
7
41
2
Order By: Relevance
“…2D electron systems in high mobility Si-MOSFET's at times have been termed clean, meaning in fact without admixture of local moments 3 , but also implicitly implying that observed properties would be disorder independent and would correspond to those of an ideally clean electron gas. This latter viewpoint, fostered by the recent experimental observation that the effective mass enhancements of samples 34,35 with peak mobilities differing by about one order of magnitude appear to be the same within error bars (of about 10%), is contradicted by our findings. We should stress indeed that the samples of Refs.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…2D electron systems in high mobility Si-MOSFET's at times have been termed clean, meaning in fact without admixture of local moments 3 , but also implicitly implying that observed properties would be disorder independent and would correspond to those of an ideally clean electron gas. This latter viewpoint, fostered by the recent experimental observation that the effective mass enhancements of samples 34,35 with peak mobilities differing by about one order of magnitude appear to be the same within error bars (of about 10%), is contradicted by our findings. We should stress indeed that the samples of Refs.…”
Section: Discussioncontrasting
confidence: 95%
“…Hence the experiment in Ref. 34 in our opinion is not at all conclusive in ruling out an effect of disorder on the effective mass, let alone on the spin susceptibility of these systems.…”
Section: Discussionmentioning
confidence: 70%
“…Anisotropy for electron transport in such samples does not exceed 5% at n s =3ϫ 10 11 cm −2 and increases weakly with electron density, staying below 25% at n s =3ϫ 10 12 cm −2 . 10 The resistance was measured by a standard four-terminal technique at a low frequency ͑5-10 Hz͒ to minimize the out-of-phase signal. The excitation current was kept low enough ͑below 2 nA͒ to ensure that measurements were taken in the linear regime of response.…”
Section: Experimental Technique and Samplesmentioning
confidence: 99%
“…[7][8][9][10] It was found in Ref. 10 by an analysis of the temperaturedependent Shubnikov-de Haas oscillations that the strongly increased mass is also the case in a dilute 2D electron system in ͑111͒ silicon with relatively high disorder, as indicated by both the absence of metallic temperature dependence of zerofield resistance and the relatively low mobility. Moreover, it was found that the relative mass enhancement as a function of r s is system and disorder independent, being determined by electron-electron interactions only.…”
Section: Introductionmentioning
confidence: 98%
“…[5][6][7] For instance, at low temperature the magnetoresistance in a parallel magnetic field was measured for a low mobility sample. 3 A MIT at a critical density N MIT Ϸ 3 ϫ 10 11 cm −2 in a g v =2 Si͑111͒ was reported using a metaloxide-semiconductor field-effect transistor ͑MOSFET͒ for a sample with a peak mobility, at low temperatures, of peak Ϸ 2.5ϫ 10 3 cm 2 / Vs. 4 Recently grown samples, [5][6][7] made with hydrogen-passivated Si͑111͒/vacuum ͓H-Si͑111͔͒ structures, had higher mobility Ϸ 2.4ϫ 10 4 cm 2 / Vs with g v =2 at low electron density and with g v = 6 at high electron density. 6 Very recently a still higher mobility Ϸ 10 5 cm 2 / Vs together with a MIT at N MIT Ϸ 0.9 ϫ 10 11 cm −2 and a valley degeneracy g v = 6 was found with H-Si͑111͒ samples.…”
mentioning
confidence: 99%